Facilitating Sexual Assault Reporting on the College Campus: The Role of Procedural Justice in Bystander Decisions to Provide Police Referrals - Henry, Tri Keah S.; Franklin, Travis W.; Franklin, Cortney A. (Violence against women, 2021)
Using a randomly assigned 2 (victim race) × 2 (alcohol consumption) between-subjects factorial design, this study used surveys from a sample of 571 undergraduate students at a mid-sized, public university in the United States to determine the effect of procedural justice on police referral after reading a sexual assault disclosure vignette. Multivariate binary logistic regression models demonstrated that positive perceptions of procedural justice increased police referral following sexual assault disclosure. Victim alcohol consumption and rape myth acceptance decreased police referral. Victim race, victim alcohol consumption, and participant sex did not moderate the effect of procedural justice on police referral. Implications are discussed.